2022
DOI: 10.1186/s12859-022-04741-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia classifier for transcriptome datasets

Abstract: Molecular gene signatures are useful tools to characterize the physiological state of cell populations, but most have developed under a narrow range of conditions and cell types and are often restricted to a set of gene identities. Focusing on the transcriptional response to hypoxia, we aimed to generate widely applicable classifiers sourced from the results of a meta-analysis of 69 differential expression datasets which included 425 individual RNA-seq experiments from 33 different human cell types exposed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We also observed that the knockout of Bhlhe40 or Arnt affected EdU incorporation in normoxic EBs. Applying a hypoxia classifier based on transcriptional changes previously developed by our group to scRNA-seq experiments in EBs, we found that in EBs under hypoxic conditions, the majority of the cells were classified as hypoxic and that in EBs under normoxic conditions, a small number of cells were also classified as hypoxic [45]. In normoxic conditions, the fraction of cells classified as hypoxic may correspond to those located in the core regions of EBs, where oxygen is compromised due to three-dimensional growth.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the knockout of Bhlhe40 or Arnt affected EdU incorporation in normoxic EBs. Applying a hypoxia classifier based on transcriptional changes previously developed by our group to scRNA-seq experiments in EBs, we found that in EBs under hypoxic conditions, the majority of the cells were classified as hypoxic and that in EBs under normoxic conditions, a small number of cells were also classified as hypoxic [45]. In normoxic conditions, the fraction of cells classified as hypoxic may correspond to those located in the core regions of EBs, where oxygen is compromised due to three-dimensional growth.…”
Section: Discussionmentioning
confidence: 99%
“…• Sheet 1: Cell metadata, including sample ID ("orig.ident"), treatment, and growth time, number of reads and genes detected, percentages of reads assigned to mitochondrial, ribosomal, and chromosome Y, cell cycle scoring results ("S.Score integrated", "G2M.Score integrated", "Phase integrated"), clustering assignment and CUS at a resolution of 0.2 ("res 0.2 Clustering", "res 0.2 Uncertainty"), hypoxia consensus predictions using the tree ensemble described in [35] ("Hx consensusPrediction"), and UMAP reduction coordinates for each cell. • Sheet 2: Clustering assignments for resolutions between 0-1.5.…”
Section: Additional Filesmentioning
confidence: 99%
“…Thus, we switched our focus to transcriptional changes occurring due to hypoxia. First, to evaluate the global effects of the treatment on the EBs we run the hypoxia classifier previously developed [35], using as input the raw counts of genes detected in the dataset. The results are displayed on a UMAP projection of the dataset in Fig.…”
Section: Hypoxia-driven Differential Expressionmentioning
confidence: 99%
See 1 more Smart Citation